Implementation Strategy for Improving Policy Quality at SMP Negeri 1 Sumenep - Sutrisno (International Journal of Science and Society, 2023)
This research aims to describe the strategies for implementing quality improvement policies, obstacles to implementing quality improvement policies, and solutions to overcome obstacles to implementing quality improvement policies at SMP Negeri 1 Sumenep. This type of research is descriptive using a descriptive qualitative approach. This research was carried out at SMP Negeri 1 Sumenep, from 19 February 2021 to 16 April 2021. The research subjects were the principal, deputy principal and teachers. Data collection was carried out by observation, interviews and documentation. Data were analyzed using the Miles and Hubberman interactive analysis model, namely data collection, data reduction, data presentation, and drawing conclusions. Meanwhile, the validity of the data was tested by triangulation of techniques and sources. The research results show the following. The strategy for implementing quality improvement policies at SMP Negeri 1 Sumenep has been running in accordance with the objectives of its establishment. This can be seen from several indicators, including standards and policy objectives that have been achieved, supporting resources, communication between school principals and teachers, employees and students running smoothly, interorganizational and inauguration activities running well, the characteristics of implementing agents support, as well as conducive social, economic and political conditions and support strategies for implementing quality improvement policies. Obstacles that arise in the implementation of quality improvement policies are: students' low understanding of the importance of education, the number of teaching staff is inadequate, learning infrastructure is inadequate, and the economic situation of students' parents is at a lower middle economic level. Solutions to overcome obstacles in implementing quality improvement policies are: providing an approach so that students want to continue their education to the next level, looking for substitute teachers according to subjects, providing infrastructure through BOS funds, providing the Smart Indonesia Program (PIP) for students who cannot afford it.